A Localized Sclerosing Osteomyelitis at the Periapex of a Vital Tooth: Report of a Misdiagnosis - Fatemeh Owlia; Mohammad-Hassan Akhavan Karbassi; Narges Mirjalili; Shokouh Taghipour Zahir; Neda Gholami; Sharare Karimi (Tabriz University of Medical Sciences, 2011)
Osteomyelitis is an inflammatory infectious condition of bones, occurring either acutely or chronically. The clinical course of the disease leads to destructive or sclerosing patterns of the involved bone. This report presents a case of chronic focal sclerosing osteomyelitis in a 19-year-old male with a history of an uncontrolled convulsive condition. The lesion was first diagnosed as an osteoblastoma. Chronic trauma or traumatic occlusion has the potential to induce osteomyelitis and should be considered a possible diagnosis in differentiating periapical radiopacities, even in relation with vital teeth.